High-strength complex-phase hot-rolled wire rod for 2200 MPa bridge cable and manufacturing method of high-strength complex-phase hot-rolled wire rod
Through the design of C-Si-Mn-Cr chemical composition and online molten salt critical quenching isothermal treatment technology, the problem of high cost of hot-rolled strip materials and difficult to control the deterioration of the tissue is solved, and the complex phase structure regulation and high-strength plastic performance matching are achieved, and the stable manufacturing of 2200MPa-level bridge cables is supported.
Patent Information
- Application Number
- CN202510180539.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-19
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2045-02-19
AI Technical Summary
During the high-strength process, existing hot-rolled strips have problems such as high material costs, difficult to control the deterioration of the tissue, insufficient strong plasticity, and large fluctuations in mechanical properties, and it is difficult to stably improve the strength level of the bridge cable.
The high-carbon chemical composition design of C-Si-Mn-Cr is adopted, combined with the critical quenching isothermal treatment technology of online molten salt, through high-temperature silk spinning and online molten salt quenching isothermal treatment, the control strips undergo phase transformation in the mixed phase zone of pearlite and martensite, regulate the complex phase structure and matrix plasticity, and reduce material costs and production energy consumption.
It has achieved simplification of the component system, reduced material costs, effectively controlled deterioration of the tissue, realized the regulation of the composite structure and matching of high-strength plastic properties, which is conducive to the stable manufacturing of 2200MPa-level bridge cables.
Smart Images

Figure CN119662951A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hot-rolled wire rods, and specifically relates to a high-strength multi-phase hot-rolled wire rod for 2200MPa-level bridge cables and a manufacturing method thereof. Background Art
[0002] With the development of modern bridge industry, bridge cables have gradually developed from the initial 1200MPa level to the 1960MPa level, and even surpassed the ultra-high strength level of 2000MPa. The ultra-high strengthening of bridge cables is conducive to the development of large span and lightweight bridges, but it is often restricted by the high strengthening limit of the hot-rolled wire rod parent material for bridge cables. In order to meet the market demand for large-span bridges, it is necessary to develop a 2200MPa-level high-strength multiphase hot-rolled wire rod for bridge cables. However, based on the current status of industrial development, the high strengthening of the hot-rolled wire rod parent material is often completed through alloying, and the wire drawing and cable making of the wire rod are completed with pearlite structure. The following technical difficulties still exist in the hot-rolled wire rod with lower material cost, better strength and plasticity and uniformity of structure: In order to achieve high strengthening of hot-rolled wire rods, the existing hot-rolled wire rods mainly increase the content of elements such as C, Si, and Mn to improve the hardenability of the wire rods, and then obtain a refined pearlite structure, i.e., a sorbite structure, on the air-cooled and controlled cooling production line after spinning to increase the sorbite content. For example, the production method of a 2100MPa steel wire rod for bridge cables disclosed in patent CN114855086A adopts a QS90SiMn composition design of C-Si-Mn-Ti-Cr-V, and combines air cooling + water mist cooling after low-temperature rolling to obtain a 95% sorbite rate, and the tensile strength of the wire rod reaches more than 1400Mpa, but the increase in alloy content The addition of precious trace alloys increases the material cost. The fine pearlite structure has good comprehensive mechanical properties, but it also limits the improvement of the strength grade of the wire rod. In order to reduce the material cost, the elements such as Ti and V are omitted, which will further reduce the strength of the wire rod. For example, the patent CN118880169A discloses a wire rod for high-strength bridge cables and a production method thereof, which adopts a high-carbon, high-silicon and high-manganese 87SiMn component system, combined with low-temperature rolling and spinning, Stylmor air-cooled line strong cooling, and insulation in an insulation corridor for more than 120 minutes to obtain a troostite content of more than 95%, and the wire rod reaches a strength of more than 1400MPa, but the strength performance is insufficient.
[0003] As the alloying degree of wire rod increases, the segregation of carbon and alloy elements in the solidification process of the steel billet will be aggravated, resulting in the generation of more deteriorated tissues, including the high carbon content component system, which is easy to form a higher level of network carbides on the air-cooled controlled cooling production line after wire drawing, which destroys the uniformity of the tissue and significantly affects the plasticity and toughness of the wire rod, increasing the risk of wire breakage in subsequent drawing. In order to minimize the adverse effects of network carbides and promote the refinement of pearlite lamellae to improve the strength of the matrix, the air-cooled controlled cooling production line adopts a combination of water mist cooling or strong air cooling treatment. However, on the one hand, the maximum cooling capacity of the air-cooled line is limited, and the improvement effect on the network carbides is limited. Although lowering the rolling wire drawing temperature is beneficial to refining the grains and strengthening the matrix, it affects the rolling efficiency, increases the wear on the rolling line, and is easy to form network carbides in the early stage of controlled cooling after wire drawing. Although increasing the wire drawing temperature is beneficial to controlling the network carbides, it will affect the grain and tissue refinement effect. It is necessary to extend the online time of the wire rod to achieve the controlled cooling effect, which is High-efficiency production is not favorable. On the other hand, with the increase of wind cooling intensity, the unstable influence of wind temperature, wind speed and air volume increases. Affected by the improvement of wire rod alloying and the segregation of alloy elements, when combined with water mist cooling, the external part of the wire rod on the same cross section is easily cooled to form quenched martensite, while the core is cooled slowly and still has the cooling effect of air-cooled line. Strong air cooling further increases the temperature difference between the windward side and the leeward side of the wire rod, and between the overlap and the non-overlap. Some positions are also prone to form abnormal martensitic structure due to overcooling, or because the austenite is not fully transformed, in the process of conventional air-cooled line cooling to below 300°C and slow cooling for a long time, the residual austenite in the wire rod structure may still undergo phase transformation into martensite, thereby leaving a martensitic structure with high hardness and high brittleness in the wire rod structure, and the mechanical properties of the wire rod fluctuate greatly and the plasticity deteriorates. At the same time, with the increase of strength grade, it is more difficult to control the deteriorated structure, which leads to the increasing risk of wire breakage during the drawing and torsion of wire rods to manufacture bridge cables. Summary of the invention
[0004] The present invention aims to solve at least one of the above-mentioned technical problems to a certain extent. The present invention provides a high-strength complex phase hot-rolled wire rod for 2200MPa grade bridge cables and a manufacturing method thereof, which can simplify the component system, reduce material costs, effectively control the deteriorated structure, realize complex phase structure regulation and high strength and plasticity matching, and is conducive to the stable manufacturing of 2200MPa grade bridge cables.
[0005] The technical solution adopted by the present invention to solve its technical problem is: A method for manufacturing a 2200MPa high-strength multiphase hot-rolled wire rod for bridge cables, the manufacturing method comprising: The wire rod is produced by rolling according to the chemical composition of the hot-rolled wire rod, wherein the chemical composition and mass percentage of the hot-rolled wire rod include: C: 0.92%~0.95%, Si: 0.55%~0.75%, Mn: 0.81%~0.95%, Cr: 0.35%~0.50%, P≤0.015%, S≤0.015%, and the rest are Fe and unavoidable impurities; the wire rod is spun into a wire rod at a spinning temperature of ≥950°C, and then subjected to online molten salt critical quenching. The wire rod is first subjected to the front-end treatment to cool down at a cooling rate of ≥38°C / s, and enters the mixed phase region of pearlite and martensite from the austenite state, promoting the transformation of part of austenite to troostite and martensite, and then undergoes the back-end treatment to reduce the circulation amount of molten salt, promote the transformation of austenite to pearlite and undergo isothermal tempering, and finally undergoes roller slow cooling to obtain a hot-rolled wire rod with a microstructure including a complex phase structure composed of tempered pearlite, tempered troostite, ferrite and tempered martensite.
[0006] The design basis of the chemical composition and mass percentage of the above hot rolled wire rod includes: (1) Carbon: As an effective carbide strengthening element and austenite forming element, C is cheaper than other alloying elements. As the carbon content increases, it is beneficial to expand the austenite phase, inhibit the formation of ferrite, and improve the matrix strength of the material. However, as the carbon content increases, it will increase the tendency of carbon segregation during the solidification of the billet, increase the tendency of decarburization and precipitation of network carbides, harm the plasticity and toughness of the steel, and reduce the effect of short-time isothermal tempering. Therefore, in order to take into account the cost and high strength requirements of 2200MPa-grade bridge cables and reduce the difficulty of controlling network carbides, the mass percentage of C is controlled to be 0.92%~0.95%.
[0007] (2) Silicon: The Si element is a deoxidizer in the steelmaking process. It can dissolve in ferrite and austenite to improve the strength of steel. At the same time, it can inhibit the tendency of grain coarsening during the previous treatment, so as to promote the rapid transformation of some high-temperature austenite structures into troostite structures and acicular martensite with smaller interlamellar spacing, thereby reducing the difficulty of isothermal tempering. However, excessive silicon content will accelerate the diffusion of carbon in steel, increase the decarburization tendency, promote the growth of columnar crystals in steel during solidification, and reduce the toughness of steel. Therefore, in order to facilitate the phase change control during online molten salt critical quenching isothermal treatment, the mass percentage of Si is controlled to be 0.55%~0.75%.
[0008] (3) Manganese: As an austenite-forming element, Mn can expand the austenite phase region and inhibit the formation of ferrite. At the same time, as an element that improves the hardenability of steel, it is beneficial to reduce the critical transformation temperature and promote the simultaneous transformation of sorbite structure and acicular martensite at a large degree of supercooling during the previous treatment process, significantly improving the matrix strength. However, when the Mn content is too high, it is easy to aggravate the segregation during the solidification process of the steel billet, which is not conducive to the control of organizational uniformity. At the same time, it reduces the activity of carbon, reduces the diffusion rate of carbon, increases the difficulty of tempering softening and the tendency of grain coarsening, and then loses the plasticity of the wire rod. Therefore, in order to take into account the high strength of the hot-rolled wire rod, facilitate the control of the complex phase structure, and reduce the difficulty of tempering control, the mass percentage of Mn is controlled to be 0.81%~0.95%.
[0009] (4) Chromium: As a solid solution strengthening element, Cr can strongly improve the hardenability of the material, shift the C curve to the right, reduce the critical cooling rate of quenching, and help refine the spacing between troostite sheets. It promotes the transformation of some austenite structures into acicular martensite during quenching, improves the matrix strength, and can also increase the work hardening rate of the wire rod during the wire drawing process, and reduce the strength loss of the subsequent wire rod made into bridge wire during the hot-dip galvanizing process. However, too high Cr content will increase the segregation of alloy elements, affect the uniformity of the wire rod structure, reduce the activity of carbon in the steel, and significantly increase the difficulty of improving the plasticity of the wire rod. It is not conducive to the short-time isothermal tempering of the complex phase structure, which in turn affects the wire drawing and torsion performance. Therefore, in order to adapt to the regulation of the complex phase structure, the mass percentage of Cr is controlled to be 0.35%~0.50%.
[0010] (5) Phosphorus and sulfur: P and S are impurity elements. The lower the better. Therefore, P is controlled to be ≤ 0.015% and S is ≤ 0.015%.
[0011] The above-mentioned hot-rolled wire rod adopts the high-carbon chemical composition design of C-Si-Mn-Cr, which can save alloy elements such as Ti and V, and replace the addition of other alloy elements with lower-priced C. The content of Si and Mn is relatively lower, which can simplify the composition system, reduce material costs and the influence of alloy element segregation. With the optimization of Si, Mn and Cr content, the critical transformation temperature can be controlled, providing favorable conditions for the phase transformation of the complex phase structure and the short-time isothermal tempering control. On this basis, a higher spinning temperature is selected to avoid the formation of network carbides in the spinning stage due to the low spinning temperature. At the same time, it is prepared for the subsequent formation of a large degree of undercooling, promoting the refinement of pearlite lamellae to obtain the sorbite structure and critical quenching. After high-temperature spinning, online molten salt critical quenching treatment is directly carried out: 1. Compared with the conventional Stelmor air-cooled line, which cannot effectively control the abnormal network carbides and martensite structures due to its limited cooling capacity, the molten salt circulation volume of the front-end treatment of the online molten salt critical quenching treatment is larger than that of the molten salt circulation volume of the back-end treatment. The high heat exchange capacity of the molten salt can be used to promote the rapid cooling of the wire rod. On the one hand, the wire rod can quickly pass through the secondary cementite precipitation temperature range of 700~800℃, thereby inhibiting the formation of network carbides, improving the adverse effects of network carbides caused by high carbon content on the uniformity and plasticity of the wire rod structure, and avoiding the effect of increasing the spinning temperature on the extension of the online time, thereby improving production efficiency. On the other hand, the wire rod can be controlled to quickly enter the narrow pearlite and martensite mixed phase region from the high-temperature austenite state. Due to the rapid cooling, a large degree of supercooling can be formed, which promotes the refinement of the pearlite lamellae and the drawing The troostite structure with good drawing performance and strong plasticity can be produced. At the same time, the wire rod is lowered to the molten salt temperature in the mixed phase zone, and part of the high-temperature austenite is controlled to be quenched and transformed into needle-shaped martensite to improve the matrix strength. When the wire rod passes through the molten salt, the molten salt can cover the surface of the wire rod for uniform and rapid heat exchange, and there is no temperature difference between the windward side and the leeward side. At the same time, strong air cooling or combined with water mist cooling process can effectively reduce the temperature difference from the edge to the core of the wire rod on the same cross section, so the troostite and martensite transformation is more uniform. At the same time, the wire rod temperature is gradually transformed to the same as the molten salt temperature, rather than continuous cooling with air cooling, which can extend the time when the wire rod is at the temperature of the mixed phase zone, promote phase transformation incubation, and then effectively control the phase transformation of the martensitic structure, so as to use the martensite, which is conventionally regarded as an abnormal structure, to improve the matrix strength and make up for the strength loss caused by simplified composition.
[0012] 2. Compared with the conventional Stelmor air-cooled line, which aims to increase the content of troostite in the organization but has insufficient strength and plasticity and uncontrollable abnormal organization, the molten salt circulation volume is appropriately reduced during the later stage of treatment. On the one hand, the supercooling degree can be appropriately reduced, and at the lower transformation temperature in the mixed phase zone, the untransformed high-temperature austenite is controlled to transform into pearlite organization with better plasticity, and the complex phase organization and matrix plasticity are regulated to promote the full transformation of austenite and avoid the residual austenite from continuing to form martensite in the subsequent cooling to destroy the organization uniformity and matrix plasticity; on the other hand, the production energy consumption can be appropriately reduced, and the molten salt temperature can be maintained so that the mixed organization including troostite, acicular martensite, pearlite and ferrite formed after the phase transformation can experience a certain degree of isothermal Tempering, since the temperature of the wire rod is consistent with the temperature of the molten salt, and the continuous cooling process without air cooling cannot be tempered due to the low temperature, the molten salt can prolong the time that the wire rod is in the mixed phase zone, that is, the high temperature isothermal zone, and provide more thermal power for tempering, thereby promoting the mixed structure to undergo short-term tempering, reduce the distortion of the acicular martensite structure, and transform the acicular martensite into a tempered martensite structure that is both strong and tough, reduce the organizational stress of troostite and pearlite, appropriately improve the organizational plasticity, obtain a tempered state organization with better plasticity, and improve the strength-plasticity matching of the wire rod. In the subsequent roller slow cooling process, the stress effect caused by the physical shrinkage of the wire rod can be reduced, and the wire rod structure can be further toughened through slow cooling, so as to achieve the regulation of the complex phase structure and the performance of the hot-rolled wire rod.
[0013] Selecting appropriate heating furnace soaking temperature and furnace time before rolling can promote uniform diffusion of alloy components, reduce segregation effects, and avoid the risk of decarburization caused by too long furnace time. In a preferred embodiment, before rolling, the heating furnace soaking temperature is controlled to be 1160~1210℃, and the furnace time is 120~180min.
[0014] Due to the high spinning temperature, the selection of a relatively high rolling temperature can increase the rolling speed, reduce the deformation resistance of the rolled piece and the wear effect on the rolling line, and at the same time control the appropriate final rolling deformation to promote dynamic recrystallization, grain refinement, and matrix toughening during the final rolling process. In a preferred embodiment, during the rolling, the initial rolling temperature is controlled to be 1110~1150℃, the final rolling temperature is 1030~1050℃, and the final rolling reduction is 25%~30%.
[0015] In a preferred embodiment, the molten salt temperature of the online molten salt critical quenching isothermal treatment is 460~500℃, the treatment time of the front-stage treatment is 40~70s, and the treatment time of the back-stage treatment is 50~200s; the molten salt temperature is in the boundary interval of the pearlite and martensite phase transformation curves. The lower the molten salt temperature and the longer the treatment time of the front-stage treatment, the refinement of the troostite lamellae and the increase of the martensite phase transformation can be promoted, and the matrix strength can be improved. However, if the molten salt temperature is too low and the front-stage treatment time is too long, the martensite phase transformation is too much, and it is difficult for the back-stage treatment to provide more thermal power for tempering, which will affect the plasticity of the wire rod and increase the production energy consumption. On the contrary, the higher the molten salt temperature and the shorter the front-stage treatment time, the lower the degree of supercooling can be, which is not conducive to the transformation of austenite to troostite and acicular martensite, and the matrix strength will be lost. The pearlite transformation increases. As the treatment time of the back-stage treatment is prolonged, the energy Provide more thermal power for tissue tempering and improve the plasticity of wire rod, but the molten salt temperature is too high and the front treatment time is too short, which affects the critical quenching effect, too little martensite phase transformation, and coarsening of troostite lamellae, which will obviously lose the strength of wire rod; the longer the treatment time of the back treatment, the better the tempering softening effect, and the plasticity of wire rod increases, but the treatment time of the back treatment is too long, which will excessively lose the strength of wire rod and increase production energy consumption. On the contrary, the shorter the treatment time of the back treatment, the lower the tempering softening effect, but the treatment time of the back treatment is too short, the martensite structure cannot be softened, which will obviously increase the brittleness of wire rod, and at the same time, the austenite structure is not fully transformed, which will increase the risk of increased mechanical fluctuations. Therefore, the molten salt temperature, the treatment time of the front treatment and the back treatment can be further controlled, so that the wire rod can obtain a complex phase structure with appropriate strong and plastic properties after the regulation of the mixed phase zone, and reduce the control difficulty and production energy consumption.
[0016] The temperature difference of the wire rod from the spinning temperature to the molten salt temperature is large. A larger molten salt circulation volume is selected for the front-stage treatment to maintain a stable molten salt temperature rise, promote rapid cooling of the wire rod and short-term phase change. In a preferred embodiment, the molten salt circulation volume of the front-stage treatment is 450~550t / h, and the molten salt temperature rise is ≤8°C.
[0017] After the wire rod is treated in the front stage, the temperature difference between the wire rod and the molten salt temperature is small. Appropriately reducing the molten salt circulation volume can appropriately reduce production energy consumption. At the same time, the molten salt temperature can be accurately controlled to promote the full phase transformation of the untransformed high-temperature austenite and a certain degree of short-term tempering. In a preferred embodiment, the molten salt circulation volume of the back-stage treatment is 255~350t / h, and the molten salt temperature rise is ≤3°C.
[0018] Compared with continuous cooling on the air cooling line, since the wire rod can fully transform after the online molten salt critical quenching isothermal treatment, it can effectively inhibit the residual austenite from continuing to transform into martensite structure. However, considering the influence of shrinkage stress, a lower roller slow cooling speed is selected before coiling to prevent the wire rod from increasing stress due to excessive cooling speed during the cooling process. At the same time, the temperature of the wire rod is relatively high after it leaves the molten salt. The use of roller slow cooling can continue the isothermal tempering effect, promote further toughening of the wire rod structure, and improve the softening effect of the wire rod. In a preferred embodiment, the roller slow cooling controls the wire rod to slowly cool to below 250°C at a cooling rate of 0.1~0.3°C / s.
[0019] In a preferred embodiment, the roller slow cooling adopts a closed insulation cover, and the hot gas generated by the online molten salt critical quenching isothermal treatment is sent into the insulation cover, and the wire rod is transported into the insulation cover by the roller, so as to recycle the production waste heat and reduce the production energy consumption.
[0020] A 2200MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables, wherein the hot-rolled wire rod is manufactured by any of the above-mentioned methods for manufacturing the 2200MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables.
[0021] The hot-rolled wire rod is designed with C-Si-Mn-Cr chemical composition. Different from the existing hot-rolled wire rod for high-strength bridge cables, which is composed of pearlite / sorbite + ferrite, the microstructure type of the hot-rolled wire rod is a composite structure composed of tempered pearlite, tempered sorbite, ferrite and tempered martensite. Pearlite has a larger interlamellar spacing and better plasticity than sorbite. After being tempered and transformed into tempered pearlite, the tissue stress can be further reduced and the matrix plasticity can be improved. The interlamellar spacing of sorbite is smaller than that of pearlite, and the strength and drawing performance are better. Good, after short-time tempering, troostite is transformed into tempered troostite, which can further reduce the tissue stress. Tempered troostite accounts for the majority, which can appropriately improve the plasticity of the matrix and is more convenient for subsequent wire drawing hardening. The needle-shaped martensite is harder than the troostite structure but more brittle. After tempering, the tissue distortion and stress are reduced, and it is transformed into tempered martensite with both strong and plastic properties. The martensite, which is conventionally regarded as an abnormal structure, is effectively utilized, which can effectively increase the strength of the wire rod, make up for the adverse effects of the simplified composition system, improve the strengthening effect of the carbon element, and improve the overall strength and plasticity of the wire rod.
[0022] The increase in the proportion of tempered pearlite and the interlamellar spacing in the complex phase structure can improve the plasticity of the matrix. In a preferred embodiment, the volume percentage of the tempered pearlite is 5% to 10%, and the interlamellar spacing of the tempered pearlite is 155 to 195 mm.
[0023] The smaller the tempered bainite interlamellar spacing and the proportion of ferrite in the multiphase structure, the higher the matrix strength can be. In a preferred embodiment, the tempered bainite interlamellar spacing is 70-110 mm, and the volume percentage of ferrite is ≤4%.
[0024] The larger the proportion of tempered martensite in the multiphase structure, the higher the matrix strength can be. In a preferred embodiment, the volume percentage of the tempered martensite is 28% to 32%.
[0025] In a preferred embodiment, the network carbide level of the hot-rolled wire rod is level 0, which can effectively avoid the deterioration effect of the network carbide on the uniformity and plasticity of the wire rod structure and improve the strengthening effect of the carbon element.
[0026] Since the network carbides in the hot-rolled wire rod are effectively controlled, the martensite is tempered and regulated, and the distribution of the complex phase structure is relatively uniform, the formation of abnormal structure due to residual austenite can be avoided, and the fluctuation of the mechanical properties of the hot-rolled wire rod structure is lower. In a preferred embodiment, the same-circle difference of the mechanical properties of the hot-rolled wire rod is ≤40MPa.
[0027] In a preferred embodiment, the diameter of the hot-rolled wire rod is 10.0~15.0mm, the tensile strength is 1568~1603MPa, and the cross-sectional shrinkage rate is 29%~34%. The hot-rolled wire rod has a high tensile strength, which is beneficial to reduce the drawing reduction rate during the unwinding, pickling, drawing, hot-dip galvanizing, and twisting processes, and quickly reach the performance level of the corresponding bridge cable. Combined with a high cross-sectional shrinkage rate, the risk of wire breakage in the subsequent wire drawing process can be reduced.
[0028] Compared with the prior art, the beneficial effects of the present invention are at least: (1) In view of the fact that the existing bridge cable hot-rolled wire rod base material is highly strengthened by alloying, it is often difficult to stably control the generation of deteriorated structure with the existing air-cooled controlled cooling production line, and the strength grade of the wire rod is limited by the pearlite structure, and the risk of wire breakage is continuously increasing, the present invention can simplify the component system and reduce the material cost by combining the C-Si-Mn-Cr chemical composition design with the online molten salt critical quenching isothermal technology, and at the same time control the wire rod after high-temperature spinning to quickly skip the secondary cementite precipitation temperature range from the high-temperature austenite state to the pearlite and martensite mixed phase region, thereby promoting part of the austenite The austenite is transformed into troostite and martensite, the strength of the matrix is improved, and the strength loss caused by the simplified composition system is compensated. At the same time, the circulation amount of molten salt is reduced, and the untransformed austenite is promoted to transform into pearlite after the wire rod is processed in the later stage and undergoes a certain degree of short-term isothermal tempering. The quenched martensite is transformed into tempered martensite with both strength and plasticity, and the tempering state of troostite and pearlite is regulated to improve the strength and plasticity matching of the wire rod. Finally, the wire rod organization is further toughened through slow cooling on a roller, which can effectively control the deterioration of the organization, realize the regulation of complex phase organization and the matching of high strength and plasticity, and has good industrial adaptability.
[0029] (2) In view of the current situation that the high-strengthened material cost of the existing hot-rolled wire rod base material of bridge cables is high, the deterioration of the structure is difficult to control, the strength and plasticity are insufficient, and the mechanical properties fluctuate greatly, the microstructure types of the hot-rolled wire rod of the present invention include a complex phase structure composed of tempered pearlite, tempered troostite, ferrite, and tempered martensite, so that the martensitic phase transformation, which is conventionally regarded as an abnormal structure, becomes controllable and can be utilized through isothermal tempering, thereby improving the strengthening effect of the carbon element. Through the combination of component design and complex phase structure regulation, the product tensile strength can reach 1568~1603MPa and the cross-sectional shrinkage rate can reach 29%~34%. It can be used in the manufacture of 2200MPa ultra-high strength bridge cables and other application fields, which is beneficial to reduce the risk of wire breakage and torsional fracture during bridge cable manufacturing, promote stable production of bridge cables, and achieve strength grade improvement, and has good market application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which: Figure 1 is a metallographic structure diagram of Example 1 of the present invention; Figure 2 It is the metallographic structure diagram of Example 2 of the present invention. DETAILED DESCRIPTION
[0031] The embodiments described below with reference to the accompanying drawings are exemplary and are only for illustration and do not limit the description of the features and characteristics of the present invention, so as to propose the best way to implement the present invention, and are intended to be used to explain the present invention and are sufficient to enable those skilled in the art to implement the present invention, but cannot be understood as any limitation on the scope of the present invention, which is limited only by the appended claims; the organization and performance testing of the hot-rolled wire rods obtained in the following embodiments and comparative examples include: the tensile test is carried out using "GB-T 228.1-2021 Metallic Material Tensile Test Part 1: Room Temperature Test Method" to obtain the tensile strength and cross-sectional reduction rate; the organization test is carried out according to the metal microstructure detection method of GB / T13298 standard; the mechanical property same circle difference test method: take 2 circles of wire rod 5m away from the end of the coil, take the overlap area position as the base point, divide each circle of wire rod into 8 sections on average, take 1 tensile specimen on each section, and the strength extreme difference of the tensile specimen after the tensile test is the mechanical property same circle difference. Embodiment 1:
[0032] A preferred embodiment of the manufacturing method of the 2200MPa grade high-strength multiphase hot-rolled wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.95%, Si: 0.55%, Mn: 0.85%, Cr: 0.45%, P: 0.013%, S: 0.013%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt critical quenching isothermal treatment → roller slow cooling → coiling, specifically: The rolling process is used to heat the steel billet with a specification of 220mm×220mm through a heating furnace to achieve a high-temperature steel billet that can be rolled into plasticity. The appropriate heating furnace temperature and furnace time are selected to promote the uniform diffusion of alloy components, reduce segregation, and control the risk of decarburization. After the steel billet leaves the heating furnace, it is rolled into a wire with a diameter of 10mm through a rolling line. The appropriate rolling temperature and deformation amount are selected to improve the rolling efficiency, promote dynamic recrystallization and refine the grains during the final rolling process. Specifically: the heating furnace soaking temperature is controlled to be 1160°C, The furnace time is 180 minutes, the initial rolling temperature is 1110°C, the final rolling temperature is 1030°C, and the final rolling reduction is 30%; the wire-spinning process is used to make the wire rods coming out of the rolling line into wire rods through a wire-spinning mechanism, and the wire rods are spread on the rollers and transported along the rollers. A higher wire-spinning temperature is selected to make the wire rods in a high-temperature austenite state to avoid the formation of network carbides in the wire-spinning stage caused by too low a wire-spinning temperature, so as to prepare for the subsequent formation of a larger undercooling degree, promote the refinement of pearlite lamellae to obtain sorbite structure and critical quenching. Specifically, the wire-spinning temperature is controlled to be 950°C.
[0033] The online molten salt critical quenching isothermal treatment process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first stage salt bath tank for front-end treatment, so that the wire rod is cooled at a cooling rate of 38°C / s, and quickly passes through the network carbide precipitation interval from the high-temperature austenite state to enter the pearlite and martensite mixed phase area, inhibiting the formation of network carbides, and promoting the transformation of part of austenite to troostite and needle-shaped martensite through short-term phase transformation through large supercooling and low transformation temperature. After that, the wire rod is conveyed by a roller through the second stage salt bath tank for rear-end treatment. The molten salt circulation volume is appropriately reduced to maintain the stability of the molten salt temperature and reduce production energy consumption. At the same time, the supercooling degree is appropriately reduced to promote the transformation of untransformed high-temperature austenite to pearlite, and control the mixed structure including troostite, acicular martensite and pearlite to undergo a certain degree of short-term tempering to improve the strength and plasticity matching of the wire rod. Specifically: the molten salt temperature is 500℃, the molten salt circulation volume of the front-stage treatment is 450t / h, the molten salt temperature rise is ≤8℃, and the treatment time is 40s; the molten salt circulation volume of the back-stage treatment is 350t / h, the molten salt temperature rise is ≤3℃, and the treatment time is 50s.
[0034] The roller slow cooling process adopts closing the insulation cover to send the hot air generated by the online molten salt critical quenching isothermal treatment into the insulation cover, and the wire rod that has passed through the second salt bath tank is transported by the conveyor roller into the insulation cover to prevent the wire rod from increasing stress due to excessive cooling speed during the cooling process, and promote further toughening of the wire rod structure, thereby improving the softening effect of the wire rod. Specifically: the wire rod is controlled to slowly cool to 248°C at a cooling rate of 0.1°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and obtain a hot-rolled wire rod product after packaging and storage. Its metallographic structure diagram is as follows Figure 1 shown.
[0035] Comparative Example 1: A method for manufacturing a hot-rolled wire rod, the manufacturing method of which is different from that of Example 1 in that: the manufacturing method is manufactured according to the process flow of rolling → spinning → Stelmor air cooling, specifically: the heating furnace soaking temperature is controlled to be 1110°C, the furnace time is 210min, the initial rolling temperature is 1055°C, the final rolling temperature is 870°C, and the spinning temperature is 840°C; the Stelmor strong air cooling adopts an air volume of 260,000 m per fan 3 / h, open 1~6# fans at 90%, cool the wire rod to 680℃ at a cooling rate of 8.8℃ / s, and then open 7~14# fans at 25%, cool the wire rod to 250℃ at a cooling rate of 3.3℃ / s. The hot-rolled wire rod is obtained after it comes off the line. The tensile strength of the hot-rolled wire rod is 1382MPa, the cross-sectional shrinkage is 21%, the microstructure includes 86% troostite by volume, the rest is ferrite and martensite, the network carbide level is 3, and the mechanical property difference is 103MPa.
[0036] Comparative Example 2: A method for manufacturing a hot-rolled wire rod, the manufacturing method differs from Example 1 in that: the heating furnace soaking temperature is controlled to be 1130°C, the furnace time is 200 minutes, the initial rolling temperature is 1075°C, the final rolling temperature is 905°C, the spinning temperature is 875°C, and the hot-rolled wire rod finished product is obtained after rolling off the line. Embodiment 2:
[0037] A preferred embodiment of the manufacturing method of the 2200MPa grade high-strength multiphase hot-rolled wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.94%, Si: 0.75%, Mn: 0.95%, Cr: 0.35%, P: 0.01%, S: 0.012%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt critical quenching isothermal treatment → roller slow cooling → coiling, specifically: The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity. Appropriate heating furnace temperature and furnace time are selected to promote uniform diffusion of alloy components, reduce segregation, and control decarburization risks. After the steel billet leaves the heating furnace, the steel billet is rolled into a wire with a diameter of 14mm through a rolling line. Appropriate rolling temperature and deformation are selected to improve rolling efficiency, promote dynamic recrystallization and refine grains during the final rolling process. Specifically: the heating furnace soaking temperature is controlled to be 1195°C, The furnace time is 140min, the initial rolling temperature is 1135℃, the final rolling temperature is 1045℃, and the final rolling reduction is 27%; the wire-spinning process is used to make the wire rods coming out of the rolling line into wire rods through a wire-spinning mechanism, and the wire rods are spread on the rollers and transported along the rollers. A higher wire-spinning temperature is selected to make the wire rods in a high-temperature austenite state to avoid the formation of network carbides in the wire-spinning stage caused by too low a wire-spinning temperature, so as to prepare for the subsequent formation of a larger undercooling degree, promote the refinement of pearlite lamellae to obtain sorbite structure and critical quenching. Specifically, the wire-spinning temperature is controlled to be 960℃.
[0038] The online molten salt critical quenching isothermal treatment process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first stage salt bath tank for front-end treatment, so that the wire rod is cooled at a cooling rate of 40°C / s, and quickly passes through the network carbide precipitation interval from the high-temperature austenite state to enter the pearlite and martensite mixed phase area, inhibiting the formation of network carbides, and promoting the transformation of part of austenite to troostite and needle-shaped martensite through short-term phase transformation through large supercooling and low transformation temperature. After that, the wire rod is conveyed by a roller through the second stage salt bath tank for rear-end treatment. The molten salt circulation volume is appropriately reduced to maintain the stability of the molten salt temperature and reduce production energy consumption. At the same time, the supercooling degree is appropriately reduced to promote the transformation of untransformed high-temperature austenite to pearlite, and control the mixed structure including troostite, acicular martensite and pearlite to undergo a certain degree of short-term tempering to improve the strength and plasticity matching of the wire rod. Specifically: the molten salt temperature is 472℃, the molten salt circulation volume of the front-stage treatment is 530t / h, the molten salt temperature rise is ≤8℃, and the processing time is 64s; the molten salt circulation volume of the back-stage treatment is 305t / h, the molten salt temperature rise is ≤3℃, and the processing time is 182s.
[0039] The roller slow cooling process adopts closing the insulation cover to send the hot air generated by the online molten salt critical quenching isothermal treatment into the insulation cover, and the wire rod that has passed through the second salt bath tank is transported by the conveyor roller into the insulation cover to prevent the wire rod from increasing stress due to excessive cooling speed during the cooling process, and promote further toughening of the wire rod structure and improve the softening effect of the wire rod. Specifically: the wire rod is controlled to slowly cool to 240°C at a cooling rate of 0.2°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and obtain a hot-rolled wire rod product after packaging and storage. Its metallographic structure diagram is as follows Figure 2 shown.
[0040] Comparative Example 3: A method for manufacturing a hot-rolled wire rod, which differs from Example 2 in that in the online molten salt critical quenching isothermal treatment process, the wire rod undergoes a front-end treatment and is cooled at a cooling rate of 42°C / s, the molten salt temperature is 450°C, and the hot-rolled wire rod product is obtained after it comes off the line.
[0041] Comparative Example 4: A method for manufacturing a hot-rolled wire rod, which differs from Example 2 in that in the online molten salt critical quenching isothermal treatment process, the wire rod undergoes a front-end treatment and is cooled at a cooling rate of 37°C / s, the molten salt temperature is 515°C, and the processing time of the back-end treatment is 240s, and the hot-rolled wire rod finished product is obtained after going offline. Embodiment 3:
[0042] A preferred embodiment of the manufacturing method of the 2200MPa grade high-strength multiphase hot-rolled wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.94%, Si: 0.75%, Mn: 0.81%, Cr: 0.44%, P: 0.015%, S: 0.012%, and the rest is Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt critical quenching isothermal treatment → roller slow cooling → coiling, specifically: The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity. Appropriate heating furnace temperature and furnace time are selected to promote uniform diffusion of alloy components, reduce segregation, and control decarburization risks. After the steel billet leaves the heating furnace, the steel billet is rolled into a wire with a diameter of 12mm through a rolling line. Appropriate rolling temperature and deformation are selected to improve rolling efficiency, promote dynamic recrystallization and refine grains during the final rolling process. Specifically: the heating furnace soaking temperature is controlled to be 1175°C, The furnace time is 165min, the initial rolling temperature is 1120℃, the final rolling temperature is 1035℃, and the final rolling reduction is 28%; the wire-spinning process is used to make the wire rods coming out of the rolling line into wire rods through a wire-spinning mechanism, and the wire rods are spread on the rollers and transported along the rollers. A higher wire-spinning temperature is selected to make the wire rods in a high-temperature austenite state to avoid the formation of network carbides in the wire-spinning stage caused by too low a wire-spinning temperature, so as to prepare for the subsequent formation of a larger undercooling degree, promote the refinement of pearlite lamellae to obtain sorbite structure and critical quenching. Specifically, the wire-spinning temperature is controlled to be 955℃.
[0043] The online molten salt critical quenching isothermal treatment process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first salt bath tank for front-end treatment, so that the wire rod is cooled at a cooling rate of 39°C / s, and quickly passes through the network carbide precipitation interval from the high-temperature austenite state to enter the pearlite and martensite mixed phase area, inhibiting the formation of network carbides, and promoting the transformation of part of austenite to troostite and needle-shaped martensite through short-term phase transformation through large supercooling and low transformation temperature. After that, the wire rod is conveyed by a roller through the second salt bath tank for rear-end treatment. The molten salt circulation volume is appropriately reduced to maintain the stability of the molten salt temperature and reduce production energy consumption. At the same time, the supercooling degree is appropriately reduced to promote the transformation of untransformed high-temperature austenite to pearlite, and control the mixed structure including troostite, acicular martensite and pearlite to undergo a certain degree of short-term tempering to improve the strength and plasticity matching of the wire rod. Specifically: the molten salt temperature is 487℃, the molten salt circulation volume of the front-stage treatment is 490t / h, the molten salt temperature rise is ≤8℃, and the processing time is 53s; the molten salt circulation volume of the back-stage treatment is 275t / h, the molten salt temperature rise is ≤3℃, and the processing time is 126s.
[0044] The roller slow cooling process adopts closing the insulation cover to send the hot air generated by the online molten salt critical quenching isothermal treatment into the insulation cover, and the wire rod that has passed through the second salt bath tank is transported by the conveying roller into the insulation cover to prevent the wire rod from increasing stress due to too fast cooling speed during the cooling process, and promote further toughening of the wire rod structure and improve the softening effect of the wire rod. Specifically: the wire rod is controlled to slowly cool to 245°C at a cooling rate of 0.15°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage.
[0045] Comparative Example 5: A method for manufacturing a hot-rolled wire rod, the manufacturing method of which is different from that of Example 3 in that the processing time of the front-end processing is 90 seconds, and a hot-rolled wire rod finished product is obtained after the production line is off the line.
[0046] Comparative Example 6: A method for manufacturing a hot-rolled wire rod, the manufacturing method of which is different from that of Example 3 in that the processing time of the front-end processing is 30 seconds, and a hot-rolled wire rod finished product is obtained after the production line is off the line. Embodiment 4:
[0047] A preferred embodiment of the manufacturing method of the 2200MPa grade high-strength multiphase hot-rolled wire rod for bridge cables of the present invention, the chemical composition and mass percentage of the hot-rolled wire rod include C: 0.92%, Si: 0.62%, Mn: 0.95%, Cr: 0.5%, P: 0.01%, S: 0.015%, and the rest are Fe and unavoidable impurities; the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt critical quenching isothermal treatment → roller slow cooling → coiling, specifically: The rolling process is used to heat a steel billet with a specification of 220mm×220mm through a heating furnace to obtain a high-temperature steel billet that can be rolled into plasticity. Appropriate heating furnace temperature and furnace time are selected to promote uniform diffusion of alloy components, reduce segregation, and control decarburization risks. After the steel billet leaves the heating furnace, the steel billet is rolled into a wire with a diameter of 15mm through a rolling line. Appropriate rolling temperature and deformation are selected to improve rolling efficiency, promote dynamic recrystallization and refine grains during the final rolling process. Specifically: the heating furnace soaking temperature is controlled to be 1210°C, The furnace time is 120min, the initial rolling temperature is 1150℃, the final rolling temperature is 1050℃, and the final rolling reduction is 25%; the wire-spinning process is used to make the wire rods out of the rolling line into wire rods through a wire-spinning mechanism, and the wire rods are spread on the rollers and transported along the rollers. A higher wire-spinning temperature is selected to make the wire rods in a high-temperature austenite state to avoid the formation of network carbides in the wire-spinning stage caused by too low a wire-spinning temperature, so as to prepare for the subsequent formation of a larger undercooling degree, promote the refinement of pearlite lamellae to obtain sorbite structure and critical quenching. Specifically, the wire-spinning temperature is controlled to be 965℃.
[0048] The online molten salt critical quenching isothermal treatment process adopts a two-stage salt bath tank with molten salt inside. The wire rod after spinning is conveyed by a roller through the first stage salt bath tank for front-end treatment, so that the wire rod is cooled at a cooling rate of 42°C / s, and quickly passes through the network carbide precipitation interval from the high-temperature austenite state to enter the pearlite and martensite mixed phase area, inhibiting the formation of network carbides, and promoting the transformation of part of austenite to troostite and needle-shaped martensite through short-term phase transformation through large supercooling and low transformation temperature. After that, the wire rod is conveyed by a roller through the second stage salt bath tank for rear-end treatment. The molten salt circulation volume is appropriately reduced to maintain the stability of the molten salt temperature and reduce production energy consumption. At the same time, the supercooling degree is appropriately reduced to promote the transformation of untransformed high-temperature austenite to pearlite, and control the mixed structure including troostite, acicular martensite and pearlite to undergo a certain degree of short-term tempering to improve the strength and plasticity matching of the wire rod. Specifically: the molten salt temperature is 460℃, the molten salt circulation volume of the front-stage treatment is 550t / h, the molten salt temperature rise is ≤8℃, and the treatment time is 70s; the molten salt circulation volume of the back-stage treatment is 255t / h, the molten salt temperature rise is ≤3℃, and the treatment time is 200s.
[0049] The roller slow cooling process adopts closing the insulation cover to send the hot air generated by the online molten salt critical quenching isothermal treatment into the insulation cover, and the wire rod that has passed through the second salt bath tank is transported by the conveying roller into the insulation cover to prevent the wire rod from increasing stress due to excessive cooling speed during the cooling process, and promote further toughening of the wire rod structure and improve the softening effect of the wire rod. Specifically: the wire rod is controlled to slowly cool to 237°C at a cooling rate of 0.3°C / s; the coiling process is used to coil the wire rod into a coil through a coiling drum, and the hot-rolled wire rod product is obtained after packaging and storage.
[0050] Comparative Example 7: A method for manufacturing a hot-rolled wire rod, the manufacturing method of which is different from that of Example 4 in that the processing time of the post-processing is 45 seconds, and a hot-rolled wire rod finished product is obtained after the production line is off the line.
[0051] Comparative Example 8: A method for manufacturing a hot-rolled wire rod, the manufacturing method differs from Example 4 in that: the manufacturing method is manufactured according to the process flow of rolling → spinning → online molten salt critical quenching isothermal treatment → air cooling, the air cooling adopts the heat preservation cover to open, the wire rod conveyed by the conveyor roller through the second section of the salt bath tank is air cooled, the wire rod is controlled to be cooled to 240°C at a cooling rate of 1.2°C / s, and the hot-rolled wire rod product is obtained after it is off the line, the tensile strength of the hot-rolled wire rod is 1611MPa, the cross-sectional shrinkage rate is 27%, the network carbide grade is 0, and the mechanical property same circle difference is 43MPa.
[0052] The hot rolled wire rods obtained in the above examples 1 to 4 and comparative examples 2 to 7 were subjected to microstructure and performance testing, and the comparative results obtained are shown in Table 1 below: Table 1. Comparison of microstructure and performance of hot rolled wire rods with different compositions and manufacturing methods
[0053] It can be seen from the comparison results of Example 1 and Comparative Example 1 that the improvement of alloying leads to the generation of more deteriorated tissues. It is difficult to stably control the generation of deteriorated tissues such as network carbides and martensite with the existing air-cooled and controlled cooling production line. At the same time, the pearlite tissue limits the improvement of the strength grade of the hot-rolled wire rod. The hot-rolled wire rod has insufficient strength and plasticity, and the mechanical properties fluctuate greatly. The risk of wire breakage during the drawing and twisting process of manufacturing bridge cables is relatively high. The present invention can effectively inhibit network carbides and control the controllable phase transformation of martensite through the C-Si-Mn-Cr chemical composition design combined with the online molten salt critical quenching isothermal technology, and through a certain degree of short-term isothermal tempering, the quenched martensite is transformed into tempered martensite with both strength and plasticity, the tempering state of troostite and pearlite is regulated, and the strength and plasticity matching of the wire rod is improved. It can be seen from the results of Examples 1 to 4 that the product tensile strength can reach 1568~1603MPa, and the cross-sectional shrinkage rate is 29%~34%, which is beneficial to reduce the risk of wire breakage and torsional fracture during bridge cable manufacturing and achieve strength grade improvement.
[0054] From the comparison results of Example 1 and Comparative Example 2, it can be seen that the online molten salt critical quenching treatment can avoid the effect of increasing the spinning temperature on the extension of the online time. Selecting a higher spinning temperature is conducive to the subsequent formation of a larger degree of supercooling, promoting the refinement of pearlite lamellae to obtain troostite structure and critical quenching to obtain a small amount of acicular martensite, thereby improving the matrix strength.
[0055] From the comparison results of Example 2 and Comparative Example 3, it can be seen that the lower the molten salt temperature and the longer the treatment time of the front stage treatment, the refinement of the troostite lamellae can be promoted, the martensitic phase transformation can be increased, and the matrix strength can be improved. However, if the molten salt temperature is too low, as the front stage treatment time is prolonged, the martensitic phase transformation is excessive, and the difficulty of tempering in the back stage treatment increases, which will affect the plasticity of the wire rod and increase the production energy consumption.
[0056] From the comparison results of Example 2 and Comparative Example 4, it can be seen that the higher the molten salt temperature, the more unfavorable the transformation of austenite to troostite and acicular martensite is, which can provide more thermal power for tissue tempering and improve the plasticity of wire rod. However, if the molten salt temperature is too high, as the processing time of the subsequent treatment is prolonged, the wire rod strength will be excessively lost, increasing production energy consumption.
[0057] From the comparison results of Example 3 and Comparative Example 5, it can be seen that using a larger molten salt circulation volume in the front-stage treatment and extending the treatment time of the front-stage treatment can increase the martensitic phase transformation and improve the matrix strength. However, if the front-stage treatment time is too long and the martensitic phase transformation is too much, the plasticity of the wire rod will be affected.
[0058] From the comparison results of Example 3 and Comparative Example 6, it can be seen that the shorter the treatment time of the front-stage treatment is, the more unfavorable the transformation of austenite to troostite and acicular martensite is, the more pearlite transformation increases, and the matrix strength will be lost.
[0059] From the comparison results of Example 4 and Comparative Example 7, it can be seen that the shorter the treatment time of the later stage treatment, the lower the tempering softening effect. If the treatment time of the later stage treatment is too short, the martensitic structure will not be softened, which will significantly increase the brittleness of the wire rod and increase the risk of increased mechanical fluctuations.
[0060] From the comparison results of Example 4 and Comparative Example 8, it can be seen that selecting a lower roller slow cooling speed before coiling can prevent the wire rod from increasing stress due to excessively fast cooling speed during the cooling process, promote further toughening of the wire rod structure, and improve the softening effect of the wire rod.
[0061] The series of detailed descriptions listed above are only specific descriptions of feasible embodiments of the present invention. They are not intended to limit the scope of protection of the present invention. All equivalent embodiments or changes that do not deviate from the technical spirit of the present invention should be included in the scope of protection of the present invention.
Claims
1. A method for manufacturing a 2200MPa grade high-strength multiphase hot-rolled wire rod for bridge cables, characterized in that: The manufacturing method thereof comprises: The wire rod is produced by rolling according to the chemical composition of the hot-rolled wire rod, wherein the chemical composition and mass percentage of the hot-rolled wire rod include: C: 0.92%~0.95%, Si: 0.55%~0.75%, Mn: 0.81%~0.95%, Cr: 0.35%~0.50%, P≤0.015%, S≤0.015%, and the rest are Fe and unavoidable impurities; the wire rod is spun into a wire rod at a spinning temperature of ≥950°C, and then subjected to online molten salt critical quenching. The wire rod is first subjected to the front-end treatment to cool down at a cooling rate of ≥38°C / s, and enters the mixed phase region of pearlite and martensite from the austenite state, promoting the transformation of part of austenite to troostite and martensite, and then undergoes the back-end treatment to reduce the circulation amount of molten salt, promote the transformation of austenite to pearlite and undergo isothermal tempering, and finally undergoes roller slow cooling to obtain a hot-rolled wire rod with a microstructure including a complex phase structure composed of tempered pearlite, tempered troostite, ferrite and tempered martensite.
2. The method for manufacturing 2200MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 1, characterized in that: Before the rolling, the heating furnace is controlled to have a soaking temperature of 1160-1210° C. and a furnace time of 120-180 min.
3. The method for manufacturing 2200MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 1, characterized in that: During the rolling, the initial rolling temperature is controlled to be 1110-1150° C., the final rolling temperature is controlled to be 1030-1050° C., and the final rolling reduction is controlled to be 25%-30%.
4. The method for manufacturing 2200MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 1, characterized in that: The molten salt temperature of the online molten salt critical quenching isothermal treatment is 460-500° C., the treatment time of the front-end treatment is 40-70 seconds, and the treatment time of the back-end treatment is 50-200 seconds.
5. The method for manufacturing 2200MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 4, characterized in that: The molten salt circulation volume of the front-end treatment is 450-550 t / h, and the molten salt temperature rise is ≤8°C; the molten salt circulation volume of the back-end treatment is 255-350 t / h, and the molten salt temperature rise is ≤3°C.
6. The method for manufacturing 2200MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 4, characterized in that: The roller slow cooling controls the wire rod to be slowly cooled to below 250° C. at a cooling rate of 0.1-0.3° C. / s.
7. A 2200MPa grade high-strength multiphase hot-rolled wire rod for bridge cables, characterized in that: The hot-rolled wire rod is manufactured by the method for manufacturing 2200MPa-grade high-strength multi-phase hot-rolled wire rod for bridge cables as described in any one of claims 1 to 6.
8. The 2200MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 7, characterized in that: The volume percentage of the tempered pearlite is 5% to 10%, the interlamellar spacing of the tempered pearlite is 155 to 195 mm, the interlamellar spacing of the tempered bainite is 70 to 110 mm, the volume percentage of the ferrite is ≤4%, and the volume percentage of the tempered martensite is 28% to 32%.
9. The 2200MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 7, characterized in that: The network carbide grade of the hot-rolled wire rod is grade 0, and the mechanical property difference is ≤40MPa.
10. The 2200MPa grade high-strength multi-phase hot-rolled wire rod for bridge cables according to claim 7, characterized in that: The hot-rolled wire rod has a diameter of 10.0-15.0 mm, a tensile strength of 1568-1603 MPa, and a cross-sectional shrinkage of 29%-34%.
Citation Information
Patent Citations
Wire rod for producting1770Mpa bridge cable galvanized steel wire and method for manufacturing same
CN101311288A
Hot-rolled wire rod for 1960 MPa bridge cable and manufacturing method of hot-rolled wire rod
CN119144802A
High-strength complex-phase hot-rolled wire rod for 1960 MPa bridge cable and manufacturing method of high-strength complex-phase hot-rolled wire rod
CN119162428A
High-strength complex-phase hot-rolled wire rod for 2060 MPa bridge cable and manufacturing method of high-strength complex-phase hot-rolled wire rod
CN119162429A
High-strength complex-phase hot-rolled wire rod for 2100 MPa bridge cable and manufacturing method of high-strength complex-phase hot-rolled wire rod
CN119265486A
Cited By
High-strength complex-phase hot-rolled wire rod for 2500 MPa bridge cable and manufacturing method of high-strength complex-phase hot-rolled wire rod
CN119913346A
A high-strength duplex hot-rolled wire rod for 2500 MPa-class bridge cables and its manufacturing method
CN119913346B
Hot-rolled wire rod for 2400 MPa bridge cable and manufacturing method of hot-rolled wire rod
CN119913347A
High-strength complex-phase hot-rolled wire rod for 2400 MPa bridge cable and manufacturing method of high-strength complex-phase hot-rolled wire rod
CN119956073A
1400 MPa-grade high-strength tool steel wire rod and manufacturing method thereof
CN120575017A